Successful Surgical Management of Grade IV Internal Hemorrhoids in a Pediatric Patient: A Case Report - Bayu Kusumo; Azzam Hizbur Rahman; Muhammad Yurizar Yudhistira (HM Publisher, 2025)
Background: Anorectal malformations are congenital conditions with a range of clinical presentations. They can be associated with portal hypertension or anatomical anomalies that obstruct venous outflow. While anorectal issues are common in pediatrics, their etiology and management can differ significantly from those in adults. This report presents a successful case of pediatric hemorrhoids managed surgically with a satisfactory outcome. Case presentation: A 4-year-old girl presented with a protruding anal lesion and intermittent constipation, first noticed at age 1. She was born aterm with no abnormalities. Physical examination revealed a 0.5 to 1 cm circular lesion obstructing the anal orifice, diagnosed as a grade-IV internal hemorrhoid. Laboratory results were within normal limits. Due to the severity of the lesion, a Whitehead hemorrhoidectomy was performed. Follow-up showed no complications, such as secondary wound healing, anal stricture, or mucosal ectropion. Conclusion: Whitehead hemorrhoidectomy is an effective treatment for severe pediatric hemorrhoids, as demonstrated by this case with a complication-free recovery. Accurate surgical technique and vigilant follow-up are key to a successful outcome.